Unraveling Enterprise Continuity and Resiliency Factors: The Case of Micro, Small and Medium Enterprises - Jonathan C Gano-an; Lotis D Cubin; Karl P Campos (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Whether an occurrence is natural disaster and man-made calamity, one thing is sure, it is not expected and at some instances, it cannot be avoided by any means. Just like other entities, businesses are vulnerable to these risks and it would surely cost the resources and profit of these enterprises. This study aimed to unravel the enterprise continuity and resiliency factors among Micro, Small, and Medium Enterprises in Region XII in the Philippines. Design/methodology/approach: The survey utilized an Exploratory Factor Analysis (EFA) with 450 respondents Findings: Results showed that there were five elements that emerged: disaster preparedness, institutional planning and control, external relations, stakeholder’s support, disaster mitigation and support investment. Research limitations/implications: Although most of the enterprises surveyed have an idea how to respond to calamities and mitigate disastrous situations, this research argues that a solid policy framework might be drawn through the local government units concerned to institutionalized this effort. Practical implications: Findings suggest that models such as pre-disaster agreement may be initiated and policy framework can be patterned after The Sendai Framework for Disaster Risk Reduction Originality/value: This paper is an original work. Paper type: Research paper